Efficacy and Synergistic Potential of Cinnamon (Cinnamomum zeylanicum) and Clove (Syzygium aromaticum L. Merr. & Perry) Essential Oils to Control Food-Borne Pathogens in Fresh-Cut Fruits - Ramona Iseppi; Eleonora Truzzi; Carla Sabia; Patrizia Messi (Antibiotics, 2024)
The presence of microbial pathogens in ready-to-eat produce represents a serious health problem. The antibacterial activity of cinnamon (Cinnamomum zeylanicum) and clove (Syzygium aromaticum L. Merr. & Perry) essential oils (EOs) was determined toward food-borne pathogens by agar disk diffusion and minimum inhibitory concentration (MIC) assays. The growth kinetics of all strains, both in a buffer suspension assay and “on food” in artificially contaminated samples, were also investigated. The two EOs demonstrated a good antibacterial effect both alone and in combination (EO/EO). The use of EO/EO led to a synergistic antibacterial effect, also confirmed by the growth kinetics studies, where the EOs were active after 10 h of incubation (p < 0.0001) at significantly lower concentrations than those when alone. In the “on food” studies performed on artificially contaminated fruit samples stored at 4 °C for 8 days, the greatest killing activity was observed at the end of the trial (8 days) with a reduction of up to 7 log CFU/g compared to the control. These results confirm the good antibacterial activity of the EOs, which were more effective when used in combination. Data from the "on food" studies suggest cinnamon and clove essential oils, traditionally used in the food industry, as a possible natural alternative to chemical additives.